Phylogenetic analysis of rubella viruses in vietnam during 2009-2010 - Tran D.N. (2014)
Rubella virus (RV) usually causes a mild disease. However, infection during the first trimester of pregnancy often leads to severe birth defects known as congenital rubella syndrome (CRS). Although wild-type RVs exist and circulate worldwide, their genotypes remain unknown in many countries. The aim of this study was to identify the molecular characteristics of RVs found in Vietnam during the years 2009-2010 and to provide the first data concerning RV genotypes in this country. Throat swab samples were collected between 2009 and 2010 from four CRS cases and nine rubella infection cases visiting one Children's Hospital and one outpatient clinic in Ho Chi Minh City. The 739-nucleotide coding region of the RV E1 gene recommended by the World Health Organization was amplified by reverse transcriptase PCR, and the resulting DNA fragments were then sequenced. Sequences were assigned to genotypes by phylogenetic analysis with RV reference strains. RV RNA was detected in 11 clinical specimens. Phylogenetic analysis of the sequences showed that all 11 strains belonged to 2B genotype. Several variations in amino acids were found, among which five changes were involved in the B and T cell epitopes. These data indicate that viruses of genotype 2B were circulating in Vietnam. The increasing information about RV genotype in Vietnam should aid in the control of rubella infection and CRS in this country. © 2012 Wiley Periodicals, Inc.